2019
DOI: 10.1177/2167479519890571
|View full text |Cite
|
Sign up to set email alerts
|

Anything Can Happen in Women’s Tennis, or Can It? An Empirical Investigation Into Bias in Sports Journalism

Abstract: The claim that “anything is possible in women’s sports” frequently employed by both sports journalists and general audiences highlights the widespread perception of a seemingly uncontested truth about female athletes and their (in)ability to perform consistently at peak levels in comparison to male athletes. We focus on this treatment of female athletes in the world of women’s tennis and contest the “common sense” and “experience” justifications of the unpredictability in women’s sports with actual data to rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Magnus and Klaassen (1999) report that, contrary to popular belief, an unseeded woman is no less likely than a man to beat a seeded opponent, while del Corral (2009) shows that such an upset is greater when it concerns an unseeded female, rather than a male, player who has formerly ranked among the top ten. Tejkalova and Kristoufek, (2019) or Du Bois and Heyndels (2007) find no evidence of lower predictability in women's match results.…”
Section: Gender As a Source Of Asymmetric Informationmentioning
confidence: 82%
“…Magnus and Klaassen (1999) report that, contrary to popular belief, an unseeded woman is no less likely than a man to beat a seeded opponent, while del Corral (2009) shows that such an upset is greater when it concerns an unseeded female, rather than a male, player who has formerly ranked among the top ten. Tejkalova and Kristoufek, (2019) or Du Bois and Heyndels (2007) find no evidence of lower predictability in women's match results.…”
Section: Gender As a Source Of Asymmetric Informationmentioning
confidence: 82%
“…Much has been examined regarding the antecedents and consequences of bias in sport (Billings, 2003; Boiché et al, 2014; Cunningham, 2010; Moskowitz & Carter, 2018; Rada, 1996; Salaga & Juravich, 2020; Stone et al, 1999; Tejkalova & Kristoufek, 2021), and an understated theme in this literature suggests that language plays a critical role in revealing such disparities (e.g., Gardner et al, 2023). Indeed, a cursory review of National Football League (NFL) draft profiles observed that writers focused on the cognitive ability of White quarterbacks more than Black quarterbacks, and the athletic ability of Black quarterbacks more than White quarterbacks (Boylan et al, 2017).…”
mentioning
confidence: 99%